CD276 regulates the immune escape of esophageal squamous cell carcinoma through CXCL1–CXCR2 induced NETs - Yu Liang; Shuang Chen; Zhi Chen; Fang Peng; Qianwen Liu; Gan Xiong; Caihua Zhang; Maosheng Cheng; Rongsong Ling; Demeng Chen; Qimin Zhou (Journal for ImmunoTherapy of Cancer)
Background CD276 (B7-H3), a pivotal immune checkpoint, facilitates tumorigenicity, invasiveness, and metastasis by escaping immune surveillance in a variety of tumors; however, the underlying mechanisms facilitating immune escape in esophageal squamous cell carcinoma (ESCC) remain enigmatic.Methods We investigated the expression of CD276 in ESCC tissues from patients by using immunohistochemistry (IHC) assays. In vivo, we established a 4-nitroquinoline 1-oxide (4NQO)-induced CD276 knockout (CD276wKO) and K14cre; CD276 conditional knockout (CD276cKO) mouse model of ESCC to study the functional role of CD276 in ESCC. Furthermore, we used the 4NQO-induced mouse model to evaluate the effects of anti-CXCL1 antibodies, anti-Ly6G antibodies, anti-NK1.1 antibodies, and GSK484 inhibitors on tumor growth. Moreover, IHC, flow cytometry, and immunofluorescence techniques were employed to measure immune cell proportions in ESCC. In addition, we conducted single-cell RNA sequencing analysis to examine the alterations in tumor microenvironment following CD276 depletion.Results In this study, we elucidate that CD276 is markedly upregulated in ESCC, correlating with poor prognosis. In vivo, our results indicate that depletion of CD276 inhibits tumorigenesis and progression of ESCC. Furthermore, conditional knockout of CD276 in epithelial cells engenders a significant downregulation of CXCL1, consequently reducing the formation of neutrophil extracellular trap networks (NETs) via the CXCL1–CXCR2 signaling axis, while simultaneously augmenting natural killer (NK) cells. In addition, overexpression of CD276 promotes tumorigenesis via increasing NETs’ formation and reducing NK cells in vivo.Conclusions This study successfully elucidates the functional role of CD276 in ESCC. Our comprehensive analysis uncovers the significant role of CD276 in modulating immune surveillance mechanisms in ESCC, thereby suggesting that targeting CD276 might serve as a potential therapeutic approach for ESCC treatment.